2012
DOI: 10.1179/2046905512y.0000000027
|View full text |Cite
|
Sign up to set email alerts
|

Association of indoor air pollution with acute lower respiratory tract infections in children under 5 years of age

Abstract: Indoor air pollution caused by using cooking fuel other than LPG and socio-economic factors are significantly associated with ALRTI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 14 publications
2
15
2
Order By: Relevance
“…Atopy, which is an abnormal production of E immunoglobulin as a response to surrounding allergens, is the strongest predisposing factor for developing asthma. Asthma exacerbation [93,94], severe respiratory symptoms [84,108], acute lower respiratory tract infections [103] and moderate airway obstruction on spirometry [109] were also observed in children due to various sources of indoor pollution (e.g., smoking, stoves, allergens, etc.) in households [87] and schools [106].…”
Section: Effects Of Exposure To Particulate Matter On Children's Healmentioning
confidence: 99%
“…Atopy, which is an abnormal production of E immunoglobulin as a response to surrounding allergens, is the strongest predisposing factor for developing asthma. Asthma exacerbation [93,94], severe respiratory symptoms [84,108], acute lower respiratory tract infections [103] and moderate airway obstruction on spirometry [109] were also observed in children due to various sources of indoor pollution (e.g., smoking, stoves, allergens, etc.) in households [87] and schools [106].…”
Section: Effects Of Exposure To Particulate Matter On Children's Healmentioning
confidence: 99%
“…Our results in Chile were consistent with several observational studies conducted in low‐ and middle‐income countries with higher prevalence of biomass fuel use. However, previously published studies have found an association between the exposure to solid fuel smoke and the occurrence of LRTI in children younger than 5 years of age and adverse pregnancy outcomes (Amegah et al., ; Lakshmi et al., ; Mahalanabis et al., ; Ramesh Bhat et al., ; Tielsch et al., ).…”
Section: Discussionmentioning
confidence: 98%
“…Other than that, this review paper did not attempt to identify intervention studies. IAP is a crucial risk factor for acute lower respiratory tract infections (ALRTI) in developing countries (19). Recent international data indicate that, currently, the increase of asthma and allergies in children is most pronounced in the more advanced developing countries (20).…”
Section: Discussionmentioning
confidence: 99%